Anti-cartel enforcement in a contemporary age : leniency religion - Beaton-Wells, Caron; Tran, Christopher (Hart studies in competition law ;, 2015)
Leniency policies are seen as a revolution in contemporary anti-cartel law enforcement. Unique to competition law, these policies are regarded as essential to detecting, punishing and deterring business collusion conduct that subverts competition at national and global levels. Featuring contributions from leading scholars, practitioners and enforcers from around the world, this book probes the almost universal adoption and zealous defence of leniency policies by many competition authorities and others. It charts the origins of and impetuses for the leniency movement, captures key insights fro.